Towards a Human Rights Based and Oriented Psychology. (September 2016) - Hagenaars, Polli
Psychologists have a societal responsibility for promoting human rights and preventing human rights violations. In 2013 a Board Human Rights and Psychology was established by the European Federation of Psychologists Associations (EFPA), in order to raise awareness of the importance of human rights for psychologists, and of psychology for human rights. In the first section a brief history of human rights is described. The Universal Declaration of Human Rights and related conventions, as the most widely accepted standards for human rights today, are taken as the starting point. The second section shows how the principles of human rights are in tune with the ethical codes of conduct of psychological associations, and a plea is made for the explicit inclusion of human rights in these codes. The third section presents a social-behavioural science perspective on human rights anchored in the Capabilities Approach of Amartya Sen and Martha Nussbaum. The fourth section describes the involvement of psychologists in a human rights based-and-oriented psychology, through research and practice, but particularly through concrete actions. The final section emphasizes the importance of human rights education for psychologists.